Cameron Lesions: A Rare and Underdiagnosed Cause of Iron Deficiency Anemia - Brites, Diana; Forra, Catarina; Ferreira, Mafalda; Sintra, Sara; Maria Eugénia (Gazeta Médica, 2025)
Iron deficiency anemia is the most common cause of anemia and can be related to gastrointestinal losses. Cameron lesions are a rare cause of chronic gastrointestinal bleeding and consequent iron deficiency anemia. It is more frequent in patients with large hiatal hernias, and the diagnosis is made through upper gastrointestinal endoscopy. Here, we present an elderly, obese woman with a large hiatal hernia, in whom lesions compatible with this pathology were detected only after several endoscopic exams, with symptomatic and analytical improvement following treatment with a proton pump inhibitor and iron supplementation. Due to the challenging diagnosis of this condition, this case report and the review of the topic highlight the importance of considering this diagnostic possibility in patients with iron deficiency anemia and large hiatal hernias, particularly during the observation of gastric mucosa in endoscopy.